Pelatihan dan Penyuluhan Pengelolaan Alokasi Dana Desa (ADD) - Bima, Muhammad Rinaldy; Kamal, Muhammad; Djanggih, Hardianto (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2020)
The problem of village fund management in 2015 and until 2018, the budget of village funds from the central government to South Sulawesi has reached a total of Rp.5.7 trillion spread over 2,255 villages. With that much budget, it should be a trigger for the performance of village officials to increase development as mandated by Law Number 6 of 2014 concerning Villages (Village Law. But in its development, the abundant village funds were prone to be misused. Based on ICW monitoring since from 2015 to 2018, cases of corruption in village funds have increased from year to year and there have been at least 181 cases of corruption in village funds with 184 suspects of corruption and a loss of Rp. 40.6 billion. Increasing abuse of village funds has also occurred in South Sulawesi, namely 22 cases have been recorded with state losses of 3.4 billion, so it is deemed necessary to take efforts through preemptive and preventive patterns so that misuse of village funds is not repeated in various regions, particularly in Baji Mangngai Village, Mandai District, Maros Regency. we make a legal study, as it is believed that jurisprudence ha dir in an effort to provide legal problem solving.